Identifying the nursing diagnosis ineffective self-health management among alcoholics: a descriptive study - Alexciane Priscila da Silva; Jaqueline Galdino Albuquerque Perrelli; Fernanda Jorge Guimarães; Suzana de Oliveira Mangueira; Simara Lopes Cruz; Iracema da Silva Frazão (Universidade Federal de Goias, 2013)
Alcoholism is a public health issue requiring important intervention from nurses providing systemized care. The objective was to identify the nursing diagnosis ineffective self-health management among alcoholics. This descriptive, cross-sectional study was performed at a hospital located in Pernambuco state. The sample consisted of 46 patients. Data collection was performed by means of structured interviews using an instrument containing information about the referred nursing diagnosis. The diagnosis Ineffective Self-Health management was identified in 28.3% of the alcoholic patients. A relationship was observed between this phenomenon and the following characteristics: Daily life choices ineffective to achieve health goals, Expression of a wish to manage the disease and Failure in reducing risk factors. The findings suggest there is a need to restructure nursing care according o these characteristics. Descriptors: Alcoholism; Nursing Process; Nursing Diagnosis; Patient Compliance.